Application of Environmental Care Character Values for Class XI Students at SMAN 13 Surabaya - Panggestu, Ibnu Graha Ade; Suhari, Suhari (Universitas Tanjungpura, 2024)
Human disregard for the environment leads to environmental issues that exacerbate natural disasters. One of the most crucial elements in developing good character in pupils is their lack of recognizing the requirement of defending the environment. In order for nation